1991
DOI: 10.1007/bf00497777
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a cytosolic inhibitor of epithelial chloride channels

Abstract: It has been known for several years that the outwardly rectifying 30-pS chloride channel, the regulation of which has been reported to be defective in cystic fibrosis, can be activated by excision of a membrane patch from a cell. This suggested that the cytosol contains an inhibitory factor, which diffuses away after excision, thereby releasing the channel block. To test for such an inhibitor we have isolated cytosol from two epithelial cell lines, and in larger quantities from pig kidney cortex. Kidney cortex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…As shown earlier, this procedure leaves the cytosolic in hibitors unaffected [17][18][19]. To enrich these inhibitors the filtrate containing heat-stable solutes was fractionated by size exclusion high-performance liquid chromatography (HPLC) using a Superose 12 column.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown earlier, this procedure leaves the cytosolic in hibitors unaffected [17][18][19]. To enrich these inhibitors the filtrate containing heat-stable solutes was fractionated by size exclusion high-performance liquid chromatography (HPLC) using a Superose 12 column.…”
Section: Resultsmentioning
confidence: 99%
“…The experiments were performed on subcontluent monolayer cultures of HT29 cells grown on collagencoated cover slips as described previously [18,19] and bathed in NaCl-Ringer solution of plasma-like ion composition. Conventional patch-clamp techniques were used to measure single channel currents in ex cised inside-out patches at room temperature usually on the first or second day of cell seeding.…”
Section: Patch-clamp Recordingmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter agrees with our present obser vations. On the other hand, it has been found that the outwardly rectifying Cl" channel can be activated by excising a membrane patch from its cell [5,19,33] which probably re flects detachment of a cytosolic inhibitor from the channel [ 18,20], This may also hold for the present experiments, since the rectify ing channel -in contrast to the bursting Cl" channel and the voltage-gated anion channel -was only observed in excised patches.…”
Section: Discussionmentioning
confidence: 47%